Augmentation of Voluntary Locomotor Activity by Transcutaneous Spinal Cord Stimulation in Motor‐Incomplete Spinal Cord‐Injured Individuals. Issue 10 (6th October 2015) - Hofstoetter, Ursula S.; Krenn, Matthias; Danner, Simon M.; Hofer, Christian; Kern, Helmut; McKay, William B.; Mayr, Winfried; Minassian, Karen
Abstract The level of sustainable excitability within lumbar spinal cord circuitries is one of the factors determining the functional outcome of locomotor therapy after motor‐incomplete spinal cord injury. Here, we present initial data using noninvasive transcutaneous lumbar spinal cord stimulation (tSCS) to modulate this central state of excitability during voluntary treadmill stepping in three motor‐incomplete spinal cord‐injured individuals. Stimulation was applied at 30 Hz with an intensity that generated tingling sensations in the lower limb dermatomes, yet without producing muscle reflex activity. This stimulation changed muscle activation, gait kinematics, and the amount of manual assistance required from the therapists to maintain stepping with some interindividual differences. The effect on motor outputs during treadmill‐stepping was essentially augmentative and step‐phase dependent despite the invariant tonic stimulation. The most consistent modification was found in the gait kinematics, with the hip flexion during swing increased by 11.3° ± 5.6° across all subjects. This preliminary work suggests that tSCS provides for a background increase in activation of the lumbar spinal locomotor circuitry that has partially lost its descending drive. Voluntary inputs and step‐related feedback build upon the stimulation‐induced increased state of excitability in the generation of locomotor activity. Thus, tSCS essentially works as an electrical neuroprosthesis augmenting remaining motor control.